The impact of environmental factors on the transport and survival of pathogens in agricultural soils from karst areas of Yunnan province, China: Laboratory column simulated leaching experiments - Ning, Zhuo; Wang, Shuaiwei; Guo, Caijuan; Zhang, Min (Frontiers in Microbiology, 2023)
Groundwater is the best candidate for drinking water supply in the karst area. Unfortunately, the important water resources are vulnerable to pathogenic microorganism contamination because of the typically thin soil layers and the high permeability of the host rock, which lead to short residence times and low natural attenuation capacities. Little attention has been paid to environmental factors affecting the pathogenic microorganism contamination in groundwater and soils in the karst area. In the study, orthogonality column experiments at different ambient temperatures, pH values of inlet water, and soil porosities were carried out to investigate the pathogenic microorganism in the leachate of agricultural soils in the karst area of Yunnan province, China. The pathogenic microorganisms, i.e. total bacteria count (TBC) and total E. coli count (TEC), as well as some hydrochemical parameters in the leaching water, were monitored. Results showed that bacteria, including E. coli, can survive a long time in karst soils under environmental conditions. The soils above the karst rocks hardly prevent the bacteria from seeping into the groundwater. On the contrary, the soils may serve as both reservoirs and incubators for pathogenic bacteria. The ambient temperature was the most key factor that affected both the TBC and TEC. Generally, the higher temperature, the higher the bacteria concentrations in the leachate. Therefore, for water supply, more attention should be paid to the temperature variations, especially in the high-temperature period, such as in the summer days.